SOME PEDAGOGICAL TECHNOLOGIES USED IN THE PROCESS OF ORGANIZING EDUCATIONAL LESSONS IN OTML (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Any pedagogical technology applied to the process of educational training, regardless of whether its components are passed through the content of the training, the textbook, textbook or the activity of the pedagogue, is required to be aimed at the development of the free and creative activity of the learner.